Determinants of Foreign Direct Investment in Indonesia: Do Presidential Regimes Matter? - Syamni, Ghazali; Ansari, Rizal; Majid, M. Shabri Abd; Marzuki, Marzuki; Akhyar, Chairil (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality: The originality of the research is the separation of data in different governments. The request is based on the leadership style, especially in the era of President Susilo Bambang Yudhoyono and President Jokowi.Research Objectives: This study examines the determinants of foreign direct investment (FDI), both in the short and long term in Indonesia during the leadership of Presidents Susilo Bambang Yudhoyono (SBY) and Joko Widodo (Jokowi).Research Methods: This study uses time series data on the World Development Indicators website from 2004 to 2021. Using Autoregressive Distributed Lag (ARDL)Empirical Results: This study finds evidence that institutional quality, economic growth, and presidential regime in the short and long run significantly positively affect FDI. Meanwhile, the population negatively influences FDI in Indonesia in both the short and long run.Implications: These findings imply that to draw in more foreign direct investment (FDI), Indonesia must enhance institutional quality, economic growth, presidential governance, and population control.JEL Classification: F21, F43, G18, H21, R23